Genetic algorithm for university course timetabling problem: application to a colombian college (2021)
University Course Timetabling Problem (UCTP) is a type of scheduling problem with a set of events and constraints that will be satisfied. A commonly used concept to tackle this problem is the genetic algorithm, which intends to simulate the Darwinian theory of evolution and the survival of the fittest to generate a viable solution to a problem. In this thesis we adapted this concept to design a mathematical model, in order to implement it through the development of a software application to serve as a measure tool that would allow us to validate the relevance of a solution to try and solve the UCTP from the Tecnológico de Antioquia, using real data and its specific constraints.